A FEMINIST POST STRUCTURAL DISCOURSE ANALYSIS OF #METOO MOVEMENT ON TWITTER - Darakhshan Anjum (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the representation of sexual violence, gender, and power in an ongoing debate on sexual violence cases reported on twitter under the #metoo movement. The main aim of this study is to explore how sexual violence, gender, and power is represented on twitter in Pakistan, and what response does the #metoo movement receives in Pakistan on Twitter. Specifically, the study explores the tweets (posts on twitter) with #metoo as a text. The methodology of manual data collection is applied to get a complete text of the tweets. The appraisal theory of systemic functional linguistic given by Martin and White (2005), is applied for analyzing the linguistic choices of 103 tweets collected in a period of 19th October 2019 till 24thOctober 2019. The textual analysis reveals that the linguistic choices in most of the tweets fall under negative appraisals regarding sexual violence, the #metoo movement, gender, and power. The analysis shows that the contexts of the selected tweets are three famous cases in Pakistan reported on twitter. First, Ali Zafar and Meesha Shafi's case, the second is MAO College Professor Mr.Afzal’s case and the third is the case of a famous director Jamshed Mehmood Raza known as Jami. Followed by Feminist Post Structural Discourse Analysis (FPDA) this research looks at sexual violence as a phenomenon that is not static and changes with time, place, and context. In analysis four different discourses are found; Discourse of Sexual Violence, Discourse of Gender, Discourse of Rejection, and Discourse of Accountability. All these discourses represent sexual violence as non-static that changes with time place and context. In the context of the present cases highlighted in analysis sexual violence is represented as a tool used for some personal gains. Like in some context there are real harassment allegations and in others, there are fake allegations that are equally damaging the society and lives of people. According to the context, gender and power relations shift. There are cases in which females are perpetrators and are at powerful positions and vice versa. The #metoo movement is unsuccessful in Pakistan as it is misused by few women for personal gains for which they use sexual violence as a tool. Similarly, in Pakistan, there are male victims of sexual violence as well as male victims accused of false allegations that not only suffer but remain unheard for so long. Therefore, there is a need for change and demand for accountability for all genders based on equality.